Performance and Security Analysis of Symmetric Data Encryption Algorithms: AES, 3DES and Blowfish - Buhari, Bello Alhaji; Abdulkadir, Hajara; Ahmad, Sadiq Aliyu; Sulaiman, Rilwanu; Umar, Maniru Malami; Shehu, Sirajo; Almu, Abba; M. Abubakar, Abdullahi; Nwoji, Jude Oguejiofor (International journal of advanced networking and applications, 2025)
In the competitive business world of today, effective use of information technologies is essential to a world's success. As a result, sharing data and information over the Internet in an information system could be risky. A comparative analysis of these algorithms is required due to the ever-changing nature of security threats and the continuous advancements in computer technology. Therefore, we evaluate the performance and security strength of AES, 3DES and Blowfish algorithms. Security strength, throughput, memory usage, and execution time are the evaluation measures. Data from text files, audio files, videos, and images were used in our research. The security study was conducted using CrypTool 2, and the performance trials were created using the Java programming language. From the experimental findings, Blowfish performed better in terms of throughput and performance for both large and small files than AES and 3DES. AES ranked second in terms of speed and throughput while maintaining a balance between security and performance. 3DES did the worst in throughput and speed. Blowfish and AES were the two algorithms with the highest memory usage. Furthermore, 3DES is a wise option in resource-constrained scenarios. AES is the most secure algorithm because it offers robust protection against numerous attacks.